2015
DOI: 10.21273/horttech.25.4.536
|View full text |Cite
|
Sign up to set email alerts
|

Nonstructural Carbohydrate Concentrations in Dormant Grapevine Scionwood and Rootstock Impact Propagation Success and Vine Growth

Abstract: Objectives of this study were to quantify starch and soluble sugar concentrations in wine grape (Vitis sp.) scionwood and rootstock material, and to examine relationships between carbohydrate (CHO) metrics and both grafting success and shoot growth. CHOs of three wine grape scionwood cultivars [Merlot and Riesling (Vitis vinifera) and Vidal blanc (Vitis sp.)] harvested from four separate vineyard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Sucrose may improve callus formation and connectivity of vascular bundles at the graft interface (Hunter et al, 2004;Ogata et al, 2005). Phillips et al (2015) suggested that in grafted grapes, an increased concentration of soluble sugars, which consisted primarily of sucrose in rootstock seedlings, could increase the survival of grafted plants. More studies are needed to evaluate different levels of sucrose concentration to optimize watermelon grafting success.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sucrose may improve callus formation and connectivity of vascular bundles at the graft interface (Hunter et al, 2004;Ogata et al, 2005). Phillips et al (2015) suggested that in grafted grapes, an increased concentration of soluble sugars, which consisted primarily of sucrose in rootstock seedlings, could increase the survival of grafted plants. More studies are needed to evaluate different levels of sucrose concentration to optimize watermelon grafting success.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon, in turn, can impact the time required for callus formation and grafting success. Bartolini et al (1996) suggested that there is a positive relationship between carbohydrate level and callus formation in grafted grape where increased carbohydrate content of rootstock seedlings led to an increase in the survival rate of grafted transplants (Phillips et al, 2015).…”
mentioning
confidence: 99%
“…The results showed that pre-grafting incubation together with upright incubation position during callusing processingincreased callus degree and percent which results in increasing scion bud break and rootstock rooting then grafting success), Since according to Rongting & Pinghai (1993 scion moisture may be positively correlated with callus formation and growththese increases and the consequently grafting success can be explained by to their effect on grafts moisture. Its effect may be similar to those obtained by hot water treatments as soaking scion wood in water for 12 hr prior to grafting ensures hydration of the plant tissues necessary for vigorous shoot growth and also, increased total sugars soluble sugars while decreased starch, total charbohydrates in some grapvine rootstocks (Phillips et al, 2015). positionposition…”
Section: Discussionmentioning
confidence: 54%
“…There are many factors involved in the grafting success such as the rooting ability of the rootstock, type of graft, fungal infection of cut surfaces and particularly callus formation (Halbrooks, 1985). Callus formation is a key factor in the development of the graft union and subsequent grafting success (Phillips et al, 2015). Carbohydrates, plant hormones (Vrsic et al, 2015 andHartmann et al, 2002), low amount of phenols and high amount of indoles are required for grafted material at grafting unionearly for successful callus formation to ensure grape grafting success (Stino et al, 2011).…”
mentioning
confidence: 99%
“…The interaction between rootstock and canopy is fundamental for the most important V. vinifera cultivars, such as Cabernet Sauvignon and Merlot, but it is less pronounced for interspecific hybrids because these materials are rustic (Barros et al 2015;Phillips et al 2015). Most cultivated hybrids are usually from crosses with North American species of Vitis, which provide better homogeneity when these varieties are grafted onto many rootstocks from the same region (Corso et al 2015;Nimbolkar et al 2016;Bascuñán-Godoy et al 2017).…”
Section: Discussionmentioning
confidence: 99%